If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -2z(z + -1) = 2z(3 + -1z) Reorder the terms: 8 + -2z(-1 + z) = 2z(3 + -1z) 8 + (-1 * -2z + z * -2z) = 2z(3 + -1z) 8 + (2z + -2z2) = 2z(3 + -1z) 8 + 2z + -2z2 = (3 * 2z + -1z * 2z) 8 + 2z + -2z2 = (6z + -2z2) Add '2z2' to each side of the equation. 8 + 2z + -2z2 + 2z2 = 6z + -2z2 + 2z2 Combine like terms: -2z2 + 2z2 = 0 8 + 2z + 0 = 6z + -2z2 + 2z2 8 + 2z = 6z + -2z2 + 2z2 Combine like terms: -2z2 + 2z2 = 0 8 + 2z = 6z + 0 8 + 2z = 6z Solving 8 + 2z = 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. 8 + 2z + -6z = 6z + -6z Combine like terms: 2z + -6z = -4z 8 + -4z = 6z + -6z Combine like terms: 6z + -6z = 0 8 + -4z = 0 Add '-8' to each side of the equation. 8 + -8 + -4z = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -4z = 0 + -8 -4z = 0 + -8 Combine like terms: 0 + -8 = -8 -4z = -8 Divide each side by '-4'. z = 2 Simplifying z = 2
| 0.9x-0.6=-0.6 | | 4x+36=4x+36 | | 21x^3-35x^2=0 | | 4x-8=2(x-5) | | 19x+87=-55+42x | | -6+d+2d=9 | | (p/3)-((3p)/8)=4 | | 4e^6x=64 | | 5=1.8Xsquared | | -5+c/4=15 | | 7l-3(4w+8)=11 | | 9(x+1)+2=4(x+8)-2x | | 3/8-8a=-5721/104 | | 1.1Q-1.5-4.8Q=-2.7Q-1.5 | | 2w+3x=10 | | 0.4*p+2=0.2*p+11 | | (p/3)-(3p)=4 | | p/3-(3p)=4 | | 4(m-6)-m=8(m-3)-5m | | ((3x)/5)-x=((x/10)-(5/2)) | | 5(3x+2)=43 | | -h/3=17 | | 2x^2+200x+198=0 | | 3x+7y-1x-4y= | | 142=5y+3x | | 9(2x-4)=2(7x+8) | | (a+1/3)-(a-1/5)=(8/15) | | -2=3(-8)-18-5(-8) | | 4/7+3/14 | | 12x-127=0 | | f(2)=7x^2-4x | | 65/13(-35/13+26/13)+(-167/13+312/13)=-1 |